Datasäädös - Koski, Heli,Pajarinen, Mika (Taloustieto Oy, 2024)
The Data Act, coming into effect in September 2025, imposes new obligations on manufacturers of connected products and providers of related services. This report provides insights into the markets affected by the Data Act and evaluates the scope of business activity it covers in Finland. Large and medium-sized enterprises subject to the Data Act had a turnover of over 44 billion euros in 2021, with a value added 14 billion euros, accounting for 5.8 percent of Finland's gross domestic product. When taking into account also small and micro-enterprises, which are subject to the obligation to provide data held by them to authorities in exceptional situations, the combined turnover of companies reaches 51 billion euros, with a value added of 17 billion euros, constituting 6.9 percent of GDP. The estimated value of data assets belonging to large and medium-sized enterprises subject to the Data Act is about 4.0-4.5 billion euros, while the estimated value of data assets of all companies is 5.6-6.2 billion euros. However, these figures are subject to uncertainty, mainly due to the interpretative ambiguity of the data regulation and issues related to statistical practices.
10419/301842
Keywords: Graue Literatur; Data Act; Regulation; Scope of business activity; Data assets